The one who stays - Blake, Toni, 1965- (Blake, Toni, 1965- Summer Island novel., 2019)
Summer Island has always been home to Meg Sloan. She runs the Summerbrook Inn, like her grandmother did, and she loves the laid-back pace of life and the close-knit community the island offers. Meg also loves Zack Sheppard, but what she doesn<U+2019>t love is Zack<U+2019>s refusal to commit to an exclusive relationship. Seth Darden arrives on Summer Island in search of summer work, but also in search of something else<U+2014>his past. There are secrets buried at the Summerbrook Inn, secrets that forged the path of Seth<U+2019>s life. But he wasn<U+2019>t counting on falling for the lovely innkeeper, Meg. When Meg meets Seth, she can<U+2019>t ignore the sparks that fly between them, even though she feels like her heart has been torn in half. But if Zack won<U+2019>t commit, should she take the leap with Seth? And can she even have a future with him if he can<U+2019>t reckon with his past?